2020
DOI: 10.1111/exsy.12521
|View full text |Cite
|
Sign up to set email alerts
|

Distributed artificial bee colony approach for connected appliances in smart home energy management system

Abstract: In this study, we propose a computational intelligence model for the Internet of Things applications by applying the concept of swarm intelligence (SI) into connected devices. Particularly, decentralized management of smart home energy management system (HEMS) is taken into account in which connected appliances, by sharing information with each other, make the individual decisions for optimizing electricity prices of smart HEMS. Specifically, the study includes two main issues: (a) We propose a framework for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The findings have shown that nABC is a promising tool for resolving UFLPs. Bui et al (2020), the artificial bee colony algorithm was used to optimize the performance of the energy management system. The smart home system has been developed and simulated to evaluate the proposed approach.…”
Section: Heuristic Optimizationmentioning
confidence: 99%
“…The findings have shown that nABC is a promising tool for resolving UFLPs. Bui et al (2020), the artificial bee colony algorithm was used to optimize the performance of the energy management system. The smart home system has been developed and simulated to evaluate the proposed approach.…”
Section: Heuristic Optimizationmentioning
confidence: 99%
“…In [117], the authors presented a decentralized HVAC management scheme where every smart device is linked by the wire connections and collaboratively interacts with others. Likewise, in [63], the authors proposed a decentralized HEMS where smart appliances communicate with each other to perform scheduling optimization based on a distributed ABC algorithm. In [113], a novel IoE communication platform was introduced to enable peer-to-peer (P2P) communications among microgrids.…”
Section: Internet Of Energy and Beyondmentioning
confidence: 99%
“…Then, the proposed approach reduced total cost by 5.44% compared with baseline ACO-based HEMS. Bui et al [63] proposed a dynamic and distributed ABC-based appliance scheduling method to minimize energy usage. By taking the IoT advantages, the appliances are connected and collaborated as a fully decentralized HEMS.…”
mentioning
confidence: 99%
“…6. A different swarm intelligence algorithm is used in the study by Bui, Agbehadji, Millham, Camacho, & Jung (2020). In this paper, the problem that is faced is the decentralized management of smart home energy management system (HEMS).…”
Section: The Paper Bymentioning
confidence: 99%
“…The authors have compared standard ant colony optimization (ACO), standard genetic algorithm (GA), ACO‐GA, which is a hybrid meta‐heuristic that uses ACO as main approach and GA as a local search procedure, and GA‐ACO, which is a memetic algorithm using GA as main approach and ACO as local search. To test the performance of these approaches, the authors have used 15 real data sets. A different swarm intelligence algorithm is used in the study by Bui, Agbehadji, Millham, Camacho, & Jung (2020). In this paper, the problem that is faced is the decentralized management of smart home energy management system (HEMS).…”
Section: Contributions Of This Issuementioning
confidence: 99%